Radiofrequency Thermal Ablation for a Small Papillary Thyroid Carcinoma in a Patient Unfit for Surgery: A Case Report - Maletta, Francesca; Garberoglio, Sara; Bisceglia, Alessandro; Ragni, Alberto; Retta, Francesca; Gallo, Marco; Garberoglio, Roberto; Papotti, Mauro (Frontiers in Endocrinology, 2021)
Ultrasound-guided radiofrequency thermal ablation has been proposed as an effective and safe procedure for treating patients who have low-risk papillary thyroid microcarcinomas and/or are unfit for surgery. We present the case of a 72-year old male patient with a small thyroid nodule diagnosed as papillary carcinoma after fine needle aspiration. Since the patient had other serious comorbidities, priority was given to other therapies and the malignant thyroid nodule was submitted to active surveillance. After detecting at a follow-up examination a slight dimensional increase of the nodule, the possibility of a radiofrequency thermal ablation was proposed to our patient, who accepted. The procedure was safely and effectively carried out. Follow-up examinations with ultrasonography (or contrast enhanced ultrasound), conducted after 1, 3, 6, and 12 months, demonstrated a progressive reduction of size and loss of vascularization in the treated area. The fine needle aspiration was repeated after 6 months: the sample revealed a very poor cellularity composed of inflammatory cells and thick colloid; no residual neoplastic cells were observed. Our experience confirmed what already demonstrated by previous reports: radiofrequency ablation can effectively eliminate small papillary carcinomas, with a very low complication rate. It may be an alternative strategy for the treatment of low-risk, indolent papillary thyroid microcarcinomas, thus avoiding the potential side-effects of surgery in patients at risk for relevant comorbidities.